PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP KETERAMPILAN MENULIS TEKS DISKUSI SISWA KELAS IX SMP MUHAMMADIYAH 1 PADANG - Khairatunnisa Khairatunnisa; Afnita Afnita (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
ABSTRACT This purpose of this study is three. First, describing the discution of writing text for students of class IX in Junior High School Muhammadiya 1 Padang using the Think Pair Share cooperative model learning, describing the discution of writing text for students of class IX in Junior High School Muhammadiyah 1 Padang using the conventional model. Third, analyzing the effect of the use of  Think Pair Share cooperative model learning on the skills of writing discution text for students of class IX in Junior High School  Muhammadiyah 1 Padang. This type of research is quantitative research with randomized two group design posttest only design experimental methods. There are three results of this study. First, the discution of writing text in IX  of Junior High School Muhammadiyah 1 Padang using the Think Pair Share cooperative model learning is of good qualification (B) with an average value of 83,37 (above of minimal completeness criteria). Second, the discution of writing text in the IX  of Junior High School Muhammadiyah 1 Padang using the conventional model with almost enough qualification (HC) with an average grade of 49,11 (under of minimal completeness criteria). Third, based on the t-test, H1 is accepted at the 95% confidence level and dk= (n1 as a numerator and n2 as denominator) because tcount>ttable (1.70 < 43.4679). Kata Kunci: Pengaruh, Model Pembelajaran Kooperatif Tipe Think Pair Share, Teks Diskusi